PERANCANGAN BUKU STORY PHOTOGRAPHY DAMAR KURUNG SRIWATI MASMUNDARI SEBAGAI APRESIASI BUDAYA SENI LUKIS TRADISIONAL GRESIK - Wardhani, Kinanthi Arum Mustika; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
Keywords: Story Photography, Damar Kurung, Sriwati Masmundari, Appreciation, Gresik, Painting, MasterpieceDamar Kurung is one of the cultural origins of traditional painting Gresik which formerly had a great history in Indonesia prior to prominence this time slowly began to fade due to modernization. That achievement was first coined by a painter named Sriwati Masmundari.In this scheme, the purpose of which is to be built by the researchers are able to design the book Story of Photography with a collection of photos of some paintings Sriwati Masmundari with its main focus on community traditions Gresik in Ramadan such as Night Market, Nuance prayer on Eid, Kedundangan and atmosphere Lebaran to be reminded again habits of any community-owned Gresik which still survive today.Some of the research methodology used is qualitative method include the following observation, interview, Existing Studies, Literature, and documentation to support the design process of the book Story Photography.From the analysis of the data obtained, the concept is